Has Personal Earnings Inequality Become Polarized? The Czech Republic in a Comparative Perspective - Mysikova, Martina (Journal of Income Distribution®, 2017)
This article analyses personal earnings distribution in the Czech Republic (CR) since the early transition from communism, using a relative distribution method. It applies data from two surveys, the national Microcensus (MC) and the European Union Statistics on Income and Living Conditions (EU-SILC), covering the period 1988–2013. The trend of “hollowing-out of the middle” was confirmed in the early transition phase, but this phenomenon later subsided. Earnings polarization was apparent for all sex and education subgroups in the Czech Republic between 1988 and 1996. Austria (AT) and Poland (PL) were selected for comparison for the longest period covered by EU-SILC, 2005–2013. While the middle was hollowing out in Austria, earnings in Poland were becoming more homogeneous.